A new species of Thaia Ghauri (Hemiptera: Cicadellidae: Typhlocybinae) from China, with a key to Chinese species - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2012)
The typhlocybine genus Thaia Ghauri, 1962 belongs to the tribe Erythroneurini with Thaia oryzivora Ghauri, 1962 as its type species. The genus consists of three subgenera: Niema Dworakowska, 1979, Nlunga Dworakowska, 1974 and Thaia Ghauri, 1962. Up to the present, 34 described species are distributed throughout the Oriental and Afrotropical regions, and some species are pests of rice. (Ghauri 1962; Song & Li 2008).